Encapsulation of Rose Extract in Polyurethane Structures Modified for Enhanced Aqueous Solubility - Ramona-Carmen Albulescu; Livia-Cristina Borcan; Florin Borcan; Camelia-Alexandrina Szuhanek (Applied Sciences)
Background: The volatile compounds present in rose extracts exhibit significant potential applications in medicine and cosmetics due to their capacity to enhance skin hydration and barrier function, two factors that are crucial for anti-aging and skin protection. The antimicrobial, anti-inflammatory, and analgesic properties of these extracts also suggest their potential utility in oral health applications. The aim of the current study was to obtain a new type of polyurethane delivery system based on a polyaddition process in the presence of a surfactant. Methods: Lysine-diisocyanate, polyethylene glycol, polycaprolactone diol, hexanediol, glycerol-1,2-diacetate, Tween® 20, and caffeine were used to synthesize two samples of PU structures, one with and one without rose extract. The structures’ shape, size and surface charge, encapsulation efficacy, pH, solubility, release kinetics, and permeation rate were all assessed; the irritation potential of samples was verified by skin parameters testing the cytotoxicity by in vitro cell viability assay. Results: Within our findings, structures measuring between 98 and 203 nm were found, while the sample containing the rose extract showed an entrapment efficacy of 71.76%. Almost 90% of the structures penetrated the membrane in 48 h, and around 45% were released from the carrier in the same period. Biosafety evaluations conducted both in vivo and in vitro confirmed that PU structures are safe as delivery vehicles. Conclusions: This study shows the potential of polyurethane structures with rose extracts for use in biomedical applications and cosmetics. However, more research is needed to examine the clinical testing of polyurethane delivery systems and optimize release kinetics and permeation rates for particular therapeutic uses.